Experimental study of contact angle and surface energy of a single aramid fibre and its relation on frictional behaviour of fibre-fibre contact - Ismail, Nurhidayah; De Rooij, Matthijn B.; Schipper, Dirk Jan; Mohd Zini, Nurul Hilwa (Malaysian Tribology Society, 2023)
Surface energy has a significant impact on the adhesion and friction behaviour of fibres in composite materials. Finding the surface energy of a single fibre, on the other hand, maybe challenging. In this work, the surface energy of single aramid fibre is calculated using dynamic contact angle measurements. The contact angles of three different types of Twaron® aramid fibres with varying treated materials and thicknesses are tested in a series of test liquids. As a result of the changing surface characteristics of the fibre, the surface energy of treated fibre is found to be approximately 37% greater than that of untreated fibre. The thickness of the fibre also affects its surface energy because thicker fibres have a larger contact area, which increases surface energy in the region of contact. At specific applied normal load conditions, it can be found that the coefficient of friction increased as the total surface energy in the area of the contact interface increased.